SYSTEMIC FAILURES IN LITHIUM-ION BATTERY FIRE FATALITIES: A CASE STUDY OF THE TERRA DRONE BUILDING - Dawaman, Muhammad; Ismara, Ima; Mujiyono, Mujiyono (LPPM Universitas Jambi, 2026)
This study analyzes a fatal fire incident at the six-story Terra Drone building in Jakarta, Indonesia, which resulted in 22 deaths due to toxic smoke inhalation. An instrumental case study, combined with root cause analysis, was employed, supported by international literature and a national regulatory review. The investigation found that the fire was triggered by the fall of a 30,000 mAh lithium polymer (LiPo) battery from a storage pile on the ground floor, initiating a thermal runaway event. The analysis identified six systemic safety management failures: absence of standard operating procedures for hazardous battery storage, lack of an occupational health and safety officer, inadequate safety training, absence of a designated storage facility, lack of fire protection systems (smoke detectors, alarms, and appropriate suppression media), and inadequate evacuation routes. The rapid release of toxic gases during Li-ion battery thermal runaway, combined with improper storage in a main evacuation path and the absence of passive and active fire protection, created a fatal scenario. The study recommends stronger regulatory enforcement, adoption of NFPA 855, multi-layer fire detection and suppression systems, and improved safety culture through training and routine audits.